Effect of electromagnetic fields and antioxidants on the trace element content of rat teeth - Dogan MS; Yavas MC; Yavuz Y; Erdogan S; Yener İ; Simsek İ; Akkus Z; Eratilla V; Tanik A; Akdag MZ (Dove Medical Press, 2017)
Mehmet Sinan Dogan,1 Mehmet Cihan Yavas,2 Yasemin Yavuz,3 Sait Erdogan,4 İsmail Yener,4 İbrahim Simsek,1 Zeki Akkus,5 Veysel Eratilla,6 Abdulsamet Tanik,7 Mehmet Zulkuf Akdag2 1Department of Pediatric Dentistry, Faculty of Dentistry, Harran University, Şanliurfa, 2Department of Biophysics, Faculty of Medicine, 3Department of Restorative Dentistry, Faculty of Dentistry, 4Department of Chemistry, Faculty of Science, 5Department of Biostatistics, Faculty of Medicine, 6Department of Prosthodontics, 7Department of Periodontology, Faculty of Dentistry, Dicle University, Diyarbakir, Turkey Abstract: The purpose of this study was to examine the possible effect of extremely low-frequency electromagnetic fields (ELF-EMFs), from a high-voltage source, on rat teeth in terms of changes in trace elements (TEs) and the effect of antioxidants (melatonin [MLT] and Ganoderma lucidum [GL]) in counteracting these effects. We used adult male Wistar albino rats with a mean weight of 250–300 g and divided the rats into eight groups. The groups were subjected to an ELF-EMF that was applied with a high-voltage line for 8 hours/day for 26 days (Groups I, II, and III) or 52 days (Groups V, VI, and VII). Groups IV and VIII were the 26- and 52-day control/sham groups, respectively. Groups II and VI were treated with GL, and Groups III and VII were treated with MLT. MLT and GL were administered daily based on the weight of the animals and appropriate standards. At the end of the study, the rats were euthanized, and their anterior teeth were extracted. The teeth were preserved in pure water before evaluating the major TEs. At the end of the study, TE concentrations (in mg/kg) were assessed in the control and test groups. Compared with Group V, statistically significant differences in the concentrations of zinc (Zn) and strontium (Sr) were found for Group VII (ELF-EMF + MLT) (P<0.05). Therefore, ELF-EMF exposure can change the content of certain TEs in teeth and, after administering MLT and GL, the values of some of the TEs return to normal. Keywords: ELF-EMF, tooth, trace element, melatonin, Ganoderma lucidum